DIGITAL INFORMATION LITERACY OF UNIVERSITY FACULTY AND RESEARCH SCHOLARS - Aarti Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The number of individuals who use the internet has increased by a factor of 11 over the course of the last seven years. As a direct result of this growth, internet cafes and cybercafés can now be found in almost every city and town throughout the whole of India. Because of the enhanced speed of the internet, these businesses are able to provide services that are not only easy to use but also reasonably priced. The onset of the digital era ushered in a period of time that brought about enormous changes to the environment of libraries and information. Because of these shifts, traditional libraries have adapted their operations to become "Knowledge Centers," with a focus on value-added electronic information services. This is a consequence of the developments that have taken place. People are considered to have digital literacy if they have the knowledge, the attitude, and the capacity to use digital tools and facilities in an appropriate way in order to search, access, manage, integrate, and assess digital resources and make media. Literacy comprises the abilities of reading and interpreting a variety of types of media, recreating data and images via the use of digital alteration, as well as analyzing and making use of newly obtained information from digital settings.